Perancangan Perangkat Lunak Dalam Perhitungan Kekuatan Memanjang Kapal - Habibi (Techno Bahari, 2019)
One of the stages in evaluating ship design is the calculation of the length of the ship's strength. Then we need a support tool that can speed up the calculation process. Therefore it is necessary to develop a program for calculation, as an alternative to evaluating the strength of the length of the ship. The study of the application of longitudinal strength of the ship aims to develop computer programs in calculating the elongated strength of the ship, analyzing and comparing the results of calculations / DelphiTM programs with the results of manual calculations, namely the use of the same formula but all calculations are done with the help of Excel®. Data process used a sampling method, which uses several ships in analyzing the strength of the shup’s length. Accuracy in the calculation of latitude for ships in calm water conditions, hogging conditions, sagging conditions in a sequence of 0.0024%; 0.0027%; 0.003%; accuracy of the calculation of the maximum moment for the vessel in calm water conditions, hogging conditions, sagging conditions in a sequence of 0,0002%; 0.0024%; 0,0002%. The maximum moment increases with increasing dimensions or size of the ship. Hopefully for further development, there will be more ivory to get more accurate calculations